Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1985
DOI: 10.1073/pnas.82.4.1136
|View full text |Cite
|
Sign up to set email alerts
|

Identification of individual interferon-producing cells by in situ hybridization.

Abstract: Individual interferon (IFN)-producing cells were identified by hybridization in situ followed by autoradiography. cDNAs corresponding to murine IFN-a and murine IFN-P labeled by nick-translation to high specific activity (24 x 10 dpm/,ug) with a-35S-labeled dATP were used as probes for hybridization with IFN mRNA in mouse C-243 cells induced with Newcastle disease virus. Control experiments with non-induced cells or with non-IFN-related labeled DNA monitored the specificity of the autoradiographic signal. Unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
2
2

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 16 publications
7
54
2
2
Order By: Relevance
“…However, when we used a DNA probe coding for a MHC class I antigen, H-2k k or a cDNA probe for /3-actin, signal distribution was much more regular. This observation is in agreement with previous studies on mouse (Zawatzky et al, 1985) and human (Enoch et al, 1986) cells and indicates that a high degree of variation in IFN mRNA content from cell to cell may be a general feature of IFN-producing cells in vitro. However, this does not necessarily imply that cells from induced cultures exhibiting only background levels of grains did not contain IFN mRNA, since in these experiments it was difficult to estimate the hybridization efficiency and accordingly the detection limit of the in situ hybridization.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, when we used a DNA probe coding for a MHC class I antigen, H-2k k or a cDNA probe for /3-actin, signal distribution was much more regular. This observation is in agreement with previous studies on mouse (Zawatzky et al, 1985) and human (Enoch et al, 1986) cells and indicates that a high degree of variation in IFN mRNA content from cell to cell may be a general feature of IFN-producing cells in vitro. However, this does not necessarily imply that cells from induced cultures exhibiting only background levels of grains did not contain IFN mRNA, since in these experiments it was difficult to estimate the hybridization efficiency and accordingly the detection limit of the in situ hybridization.…”
Section: Discussionsupporting
confidence: 82%
“…Following hybridization, the slides were washed in three changes of 1 x SSC/50~ formamide at 42 °C (IFN-ct and -/3 probes) or 30 °C (H-2k k and chicken/3-actin probe) for 2 h, dehydrated with increasing concentrations of ethanol and dried overnight. Autoradiography was performed as described (Zawatzky et al, 1985). For microscopic evaluation, grains on an average of 100 cells with intact morphology were counted.…”
Section: Introductionmentioning
confidence: 99%
“…This explains why only a fraction of the HeLa-C-127 and 143 tk--C-127 heterokaryons express human f-IFN mRNA. Heterogeneity in the expression of aand ,B-IFN in response to induction has also been reported in mouse C-243 cells (49). Variation in the responses of individual cells to inducers may be a general property of the IFN system.…”
Section: Discussionmentioning
confidence: 95%
“…In this system, single-cell analysis showed that only a small number of cells have elevated levels of endogenous b-globin mRNA, suggesting stochastic activation of the native b-globin promoter. Similarly, expression of IFN-b in response to viral infection in humans is stochastic, with only a subset of the cells of a population showing detectable transcript (Zawatzky et al 1985). A recent analysis has led to a model wherein IFN-b expression depends on interchromosomal associations between multiple unlinked loci, which occur only in a subset of cells (Apostolou and Thanos 2008).…”
Section: Gmr Action In Trans Is Variegatedmentioning
confidence: 99%